أهمية تدريس القصة في سيطرة الطلبة على مهارة الكلام (في مدرسة هارابان بنجسا الثانوية الإسلامية الأهلية مولابوه) - Aan Muhammady; Ayuni Saputri ('ARABIYYA: JURNAL STUDI BAHASA ARAB, 2017)
Maharah kalam is one of four language skills to be mastered by a learner. Among the various methods available, teaching with story methods is the most influential in improving the ability of learners. This has been proven from the results of research as follows: 1. students' ability in speaking increases and their interest in learning Arabic to be better. 2. the increase of students' values as their ability to master speech skills. This study uses classroom action research that is conducted in order to prove the effectiveness of teaching methods of language with storytelling